2012
DOI: 10.1038/nature11624
|View full text |Cite
|
Sign up to set email alerts
|

An ultraviolet-radiation-independent pathway to melanoma carcinogenesis in the red hair/fair skin background

Abstract: People with pale skin, red hair, freckles, and an inability to tan—the “redhair/fairskin” phenotype— are at highest risk of developing melanoma, compared to all other pigmentation types1. Genetically, this phenotype is frequently the product of inactivating polymorphisms in the Melanocortin 1 receptor (MC1R) gene. MC1R encodes a cAMP stimulating G-protein coupled receptor that controls pigment production. Minimal receptor activity, as in redhair/fairskin polymorphisms, produces red/yellow pheomelanin pigment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
391
3
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 427 publications
(450 citation statements)
references
References 30 publications
25
391
3
7
Order By: Relevance
“…In those persons with fair skin and red hair, specific mutations at the MC1R gene are responsible for the switch from eumelanin to phaeomelanin, inducing increased oxidative stress and higher risk of melanoma [35,36]. In a similar manner, it was demonstrated that recessive yellow mice with loss-of-function MC1R were developing more invasive melanoma than their albino counterparts [75].…”
Section: Melanomasupporting
confidence: 49%
“…In those persons with fair skin and red hair, specific mutations at the MC1R gene are responsible for the switch from eumelanin to phaeomelanin, inducing increased oxidative stress and higher risk of melanoma [35,36]. In a similar manner, it was demonstrated that recessive yellow mice with loss-of-function MC1R were developing more invasive melanoma than their albino counterparts [75].…”
Section: Melanomasupporting
confidence: 49%
“…Byproducts of LPO could react with DNA to generate exocyclic adducts, including 1,N 6 -etheno-2Ј-deoxyadenosine (dA) and 1,N 2 -etheno-2Ј-deoxyguanosine (dG) (5,6). Multiple lines of evidence showed that these DNA lesions in mammalian cells, tissues and blood may serve as potential biomarkers of oxidative stress (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: -Etheno-2-deoxyguanosine (Dg) Analysis Of Liver Tissues Of mentioning
confidence: 99%
“…This demonstrates complexion matters, as the oxidative-damage-repair pathways may have a role in the pathogenesis of MM. 13 In the next section, new studies related to the role of sunlight and MM are reviewed.…”
Section: Birth Of Nevi and Nevi At Birth: Timing Of Mutationsmentioning
confidence: 99%
“…12 The role for ROS in generating DNA mutations in MM, regardless of the exposure to sunlight, has gained momentum due to recent findings with red-hairbearing mice (so-called ginger mice), in which pheomelanin predominates over eumelanin. 13 Using genomically distinct strains of mice, it was demonstrated that there might be an ultraviolet radiation-independent pathway to MM carcinogenesis. The pigmentation phenotype resulting from the ratio of pheomelanin to eumelanin reflects polymorphisms in the melanocortin 1 receptor (MC1R) gene and in tyrosinase gene activity that can lead to a UV-radiation-independent carcinogenesis in mice.…”
Section: Birth Of Nevi and Nevi At Birth: Timing Of Mutationsmentioning
confidence: 99%